2013
DOI: 10.1097/bor.0b013e32835b1366
|View full text |Cite
|
Sign up to set email alerts
|

Biologics-induced autoimmune diseases

Abstract: As the use of biological therapies expands, the number and diversity of induced autoimmune disorders should be expected to increase. Paradoxically, for many of these drug-related processes, current treatment indications include the very biological agent producing the adverse event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 59 publications
2
103
0
9
Order By: Relevance
“…RA can have cardio-vascular manifestations since it has been reported that rheumatic diseases could be associated to increased carotid intima-media thickness when explored by a two-dimensional echo-colour Doppler of the carotid arteries [1,2]. The other extraarticular cardio-vascular manifestation reported in RA is vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…RA can have cardio-vascular manifestations since it has been reported that rheumatic diseases could be associated to increased carotid intima-media thickness when explored by a two-dimensional echo-colour Doppler of the carotid arteries [1,2]. The other extraarticular cardio-vascular manifestation reported in RA is vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a good overall safety profile, they can induce a number of adverse effects, including autoimmunity and infections [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatol. (2017) 12 (6) To the best of our knowledge there is no controlled animal histopathological study demonstrating the effect of adalimumab on the kidney.…”
Section: Research Articlementioning
confidence: 99%
“…Biological agents have been related with the development of advert events including autoimmune process [20]and physicians should bear this in mind when biosimilars are postulated as therapies for autoimmune diseases. Impurities in biological products, structural modifications resulting from the manufacturing and/or suboptimal storage conditions can increase the risk of immunogenicity, leading to the possible production of antibodies against any biosimilar component [21].…”
Section: Immunogenecitymentioning
confidence: 99%